PTX3 as a diagnostic and prognostic biomarker in lung adenocarcinoma: a comprehensive analysis - Shaobo Zhou; Na Li; Dina Haishaer; Hongmei Zhao (Discover Oncology)
Abstract Background Lung cancer remains a leading global cause of mortality, with lung adenocarcinoma (LUAD) as the predominant histological subtype. Current serum biomarkers like carcinoembryonic antigen (CEA) lack specificity, necessitating novel diagnostic targets. Pentraxin 3 (PTX3), a homo-multimeric protein downregulated in malignancies, was evaluated for its diagnostic and prognostic roles in LUAD. Methods PTX3 expression was analyzed using TCGA/GEO datasets and clinical serum samples (97 LUAD vs. 40 controls). Diagnostic utility was assessed via ROC curves for PTX3, CEACAM5, and their combination. Prognostic value was determined by Kaplan-Meier and Cox regression. PTX3-associated differentially expressed genes (DEGs) were explored through functional enrichment, tumor microenvironment (TME) analysis, and drug sensitivity profiling. Result The TCGA and GEO datasets revealed that PTX3 mRNA expression was significantly downregulated in LUAD, and the AUC values with PTX3 were > 0.7. Detection of CEACAM5 and PTX3 combined can improve diagnostic accuracy, and patients with high PTX3 level have shorter overall survival. Multivariate Cox analysis revealed that PTX3 is an independent predictor of overall survival. The result of ELISA further confirmed the low level of PTX3 protein. PTX3 is important in the functional analysis and TME of lung adenocarcinoma. In addition, the sensitivity of tumor cells to anti-cancer drugs is significantly correlated with the expression of PTX3. Conclusion PTX3 emerges as a dual biomarker for LUAD diagnosis and prognosis, with mechanistic ties to TME remodeling and therapeutic resistance, highlighting its potential for clinical translation.